Quality of giant freshwater prawn (Macrobrachium rosenbergii) during the storage at −18°C as affected by different methods of freezing. Issue 1 (1st January 2018) - Yu, Lixia; Jiang, Qixing; Yu, Dawei; Xu, Yanshun; Gao, Pei; Xia, Wenshui
ABSTRACT: This study investigated the effects of liquid nitrogen quick-freezing, −35°C air-blast freezing, and −18°C refrigerator direct-freezing on quality retention of frozen giant freshwater prawns using various indicators: microscopic structure, physicochemical, texture, and color properties. The results showed that the shelf lives of prawns treated with liquid nitrogen quick-freezing, −35°C air-blast freezing, and −18°C refrigerator direct-freezing were about 20, 12, and 8 weeks, respectively, in terms of total volatile basic nitrogen content and K -value. Meanwhile, liquid nitrogen quick-freezing could effectively improve texture property of frozen giant freshwater prawn. These findings confirm that liquid nitrogen quick-freezing is a promising method to extend the shelf life of frozen prawns.